Magnetic structures developed under milling in Al0.4Fe0.6 - Mendoza Zélis, Luis Alejandro (2000)
The intermetallic compound Al0.4Fe0.6 in its ordered B2 phase has been ground under Ar in a ball-milling device up to the completion of the solid state reaction when a steady state was reached. The system transformation has been examined by X-ray diffraction and transmission Mössbauer spectroscopy, which show the development of two magnetic subspectra as milling progresses. The evolution of these magnetic components under annealing treatments at moderate temperatures was followed by Mössbauer spectroscopy and differential scanning calorimetry. The associated magnetic structures are interpreted in terms of creation and recovery of antiphase boundaries and antisite defects.